Risk of sarcopenia in older adults with type 2 diabetes mellitus: evaluation of the SARC-F and SARC-CalF as screening tools - Amanda de Azevedo Araújo; Ilma Kruze Grande de Arruda; Maria da Conceição Chaves de Lemos; Nathalia Karolyne de Andrade Silva (Brazilian Society of Geriatrics and Gerontology, 2023)
Objective: To evaluate the diagnostic power of SARC-F and SARC-CalF as screening tools for sarcopenia risk in older adults with type 2 diabetes mellitus. Methods: This cross-sectional study of 128 patients was conducted at the endocrinology outpatient clinic of a hospital in Recife, Brazil between July 2022 and February 2023. Sarcopenia was diagnosed according to original and updated European Consensus criteria for older adults. Muscle mass was assessed with electrical bioimpedance, muscle strength was assessed with a handgrip test, and physical performance was assessed with gait speed. Sarcopenia risk was assessed using the SARC-F and SARC-CalF instruments. The sensitivity, specificity, positive and negative predictive values, receiver operating characteristic curve, and area under the curve were analyzed to determine the best diagnostic performance. Results: According to the original and updated versions of the European Consensus criteria, the prevalence of sarcopenia was 25.00% and 10.90%, respectively. Sarcopenia risk was 17.20% according to the SARC-F and 23.40% according to the SARC-CalF. The sensitivity and specificity of the SARC-F ranged from 12.55% to 36.11% and 71.87% to 92.39%, respectively,while those of the SARC-CalF ranged from 47.22% to 85.71% and 82.46% to 88.89%,respectively. The area under the curve for the SARC-F and SARC-CalF varied between 0.51 and 0.71 and 0.67 and 0.86, respectively.Conclusions: The SARC-CalF had better diagnostic performance for all analyzed diagnostic criteria. Adding calf circumference to the SARC-F was an effective screening method for sarcopenia risk in the study population.